Reproductive performance of Macrobrachium acanthurus (Crustacea, Palaemonidae) females subjected to unilateral eyestalk ablation - Maschio Rodrigues, Maria [UNESP]; López Greco, Laura S.; Almeida, Luis Carlos Ferreira de [UNESP]; Bertini, Giovana [UNESP] (Wiley, 2021)
The present study investigated the effects of eyestalk ablation on the reproductive performance of females from the native caridean shrimp Macrobrachium acanthurus. The reproduction parameters fertility, fecundity, egg volume, larvae size, loss of embryos and number of females with viable eggs/larvae were evaluated. Females presenting carapace length of 12–15 mm and spent stage of gonadal development were divided into two groups, one undergoing unilateral eyestalk ablation and the other remaining intact. The specimens were kept in aquarium until ovarian maturation, then brought together with males for mating (proportion of two females for each male). Fecundity and fertility were greater in intact females (1,741 eggs and 1,045 larvae) than in ablated ones (1,373 eggs and 741 larvae). Ablation also reduced the percentage of females with viable eggs (68% intact versus 49% ablated) and larvae (82% intact versus 64% ablated), besides increasing the loss of embryos. Egg volume and shape (ellipsoid) and larvae size were similar, as was the duration of embryonic development. The results of this study suggest that, although ablated females exhibit a high rate of survival, their reproductive performance is reduced; therefore, the ablation technique is not recommended in M. acanthurus farming, so as to protect the animals from physiological stress.
Keywords: captivity; cinnamon river shrimp; fecundity; fertility; spawning